2014
DOI: 10.1097/meg.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Faecal analysis and plasma complement factor 3c levels at admission for an acute attack of ulcerative colitis are predictive of the need for colectomy

Abstract: Early faecal analysis and measurement of complement factor 3c may be useful as predictive markers of the need for colectomy related to a severe attack of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In early clinical studies, complement activation was shown to be associated with the progression of UC and CD. The synthesis of complement components in the intestine of UC patients might be part of the local inflammatory amplification process . In our study, we found that serum FCN‐2/A increased in both patients with IBD and in mice with acute colitis.…”
Section: Discussionmentioning
confidence: 99%
“…In early clinical studies, complement activation was shown to be associated with the progression of UC and CD. The synthesis of complement components in the intestine of UC patients might be part of the local inflammatory amplification process . In our study, we found that serum FCN‐2/A increased in both patients with IBD and in mice with acute colitis.…”
Section: Discussionmentioning
confidence: 99%